THE APPLICATION OF PROMETHEE AND BORDA METHODS FOR SELECTING BUSINESS LOCATION - Sutikno Wahyu Hidayat; I Nengah Putra A; Ike Agustiyani; Adi Bandono (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The development of a franchise business requires the opening of new branches to be able to expand the wider market in the community. The selection of a franchise's new location is a very decisive factor in the success of the franchise in the future. With the new location allows to increase the range, market and number of consumers. The object of research in this case is a retail franchise. The PROMETHEE method is used to manage individual decisions of each decision maker, while the Borda method is used to manage group decisions on the results of the PROMETHEE method ranking. The use of these two methods is one solution to produce more objective group decisions. Alternative ranking of this location is in accordance with the rules and policies and procedures for opening a new branch of a retail franchise. The variables in this study are facilities and infrastructure, crime, per capita income, economic growth, population and the number of retail franchises around the alternative location for opening the retail franchise branch. The results obtained from this study are location E or Endrosono area as the best alternative location.